The Effect Of Addition Skipjack Tuna On The Quality Of Wet Corn Noodles - Anwar, Noviana; Holinesti, Rahmi; Mustika, Sari (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
Wet corn noodles are a food product made from wheat flour with the addition of corn flour. This research aims to analyze the effect of adding 10% skipjack tuna on the quality of shape, color, texture, aroma and taste of wet corn noodles. This type of research is experimental using the Independent Sample T-test method. The data used is primary data obtained directly from three expert panelists by filling in the organoleptic test format for the quality of wet corn noodles with the addition of skipjack tuna and secondary data from journals. The data obtained was then tabulated in table form and a level test was carried out on each variable X1 and X2 to find out whether there was a mean comparison for these variables using the Independent Sample T-test. The results of this research show that there is an effect of adding 10% of skipjack tuna on the quality of shape, color, texture, aroma and taste. The results of data analysis obtained the highest overall achievement scores, namely neat shape quality 3.78 (quite neat), uniform shape quality 3.89 (quite uniform), color quality 2.78 (less yellow), springy texture quality 3.67 (fair chewy), easy to break texture quality 2.22 (less easy to break), aroma quality 3.78 (quite a typical wet noodle aroma), taste quality 3.78 (quite tasty). Test results for the best quality of wet corn noodles with the addition of skipjack tuna in treatment X2 with the addition of 10% skipjack tuna.